Broadband Heteronuclear Spin Decoupling in Solids - Suter, Dieter; Pines, Alexander; Lee, J. H.; Drobny, G. (Elsevier, 2001)
Experimental results demonstrate that recently introduced COMARO decoupling sequences can be used for broadband heteronuclear decoupling in solids, providing decoupling performance that is considerably less sensitive to off-resonance effects than cw decoupling and allowing good decoupling with relatively low rf power.
Keywords: 530